A randomized–controlled study to compare the efficacy of sequential therapy with standard triple therapy for Helicobacter pylori eradication in an Irish population. Issue 11 (November 2015) - Haider, Rana B.; Brennan, Denise E.; Omorogbe, Joseph; Holleran, Grainne; Hall, Barry; O'Morain, Colm; Breslin, Niall; O'Connor, Humphrey J.; Smith, Sinead M.; McNamara, Deirdre
<x xml:space="preserve">Abstract</x> Introduction Eradication rates for the standard first-line triple therapy for Helicobacter pylori infection have decreased in recent years. Sequential therapy has been suggested as an alternative. The efficacy of sequential therapy has not been assessed to date in an Irish population. Objective The aim of this study was to compare the efficacy of standard triple therapy with sequential therapy for H. pylori eradication. Patients and methods A prospective randomized–controlled study was carried out. Treatment-naive H. pylori-infected patients were randomized to receive either standard triple therapy or sequential therapy. Results In all, 87 eligible patients were recruited into the study, one of whom dropped out. Fifty-one per cent (N=44) patients received standard triple therapy and 49% (N=42) patients received sequential therapy. The eradication efficacy by intention-to-treat analysis was 56.8% [N=25/44; 95% confidence interval (CI) 42.2–71.4%] for standard triple therapy and 69% (N=29/42; 95% CI 55.0–83.0%) for sequential therapy. The eradication rates by per-protocol analysis for standard triple therapy and sequential therapy were 61% (N=25/41; 95% CI 46.1–76.0%) and 69% (N=29/42; 95% CI 55.0–83.0%), respectively. The differences in eradication rates for each treatment by either intention-to-treat or per-protocol analysis were not statistically significant (P=0.24 and 0.44, respectively). In addition, incidence in adverse events was not significantly different between the study groups. The most common adverse event reported was mild nausea at 15% (95% CI 7.5–22.6%). Conclusion Sequential therapy had a nonstatistically significant advantage over standard triple therapy in our patient cohort. However, eradication rates for both standard triple therapy and sequential therapy were suboptimal. Further studies are required to identify potential alternatives to standard first-line triple therapy.